(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Postoperative knee bracing is traditionally used after anterior cruciate ligament reconstruction (ACLR) to protect the graft by limiting excessive knee motion. However, evidence regarding its efficacy in enhancing stability and functional recovery remains conflicting. Objective: To compare postoperative stabilizing knee foot orthosis versus no orthotic intervention on knee stability, function, and rehabilitation outcomes after ACLR. Methods: In this randomized controlled trial, 86 patients undergoing bone–patellar tendon-bone ACLR were allocated to a braced group (n=43) or a non-braced group (n=43). Both groups followed a standardized rehabilitation program for six months. Outcomes included instrumented laxity, isokinetic muscle strength, one-leg hop test, range of motion (ROM), knee circumference, Lysholm score, Tegner activity score, and visual analogue scale (VAS) for pain/instability. Data were collected preoperatively and at 3- and 6-month follow-ups. Results: No significant differences were observed between groups for knee laxity, ROM, isokinetic torque, or hop performance (p>0.05). The non-braced group demonstrated smaller knee circumference at 3 months and higher Tegner activity scores at 3 and 6 months (p<0.01). Both groups achieved excellent Lysholm scores (>90) and low VAS scores by 6 months, with no intergroup differences. Conclusion: Postoperative bracing after ACLR did not provide superior stability, pain control, or functional outcomes compared with no orthotic intervention. These findings suggest that routine use of postoperative knee braces may not be necessary, allowing simplified rehabilitation without compromising patient outcomes.